Analisis Beban Kerja Fisik Menggunakan Metode Cardiovascular Load (CVL) pada Area Finishing (Studi Kasus di Salah Satu Perusahaan Logam di Klaten, Jawa Tengah) - Dyah Ari Susanti; Dinda Pangesti (INDUSTRIAL ENGINEERING JOURNAL of the UNIVERSITY of SARJANAWIYATA TAMANSISWA, 2021)
The purpose of this research is to find the physical workload of one of the Metal Industry in Klaten, Jawa Tengah, Indonesia and find best recommendations to company. The method used in this study is Cardiovascular Load (CVL) to measure physical workload for each employee in finishing deparment. Physical workload measured by calculate pulse while work and heart pulse while rest, maximum heart pulse and age of the employee. The conclusion of this research is among sixteen employees in the finishing department, eight people (50%) experience fatigue and another 50% not experience fatigue. The recommendations for the company to reduce fatigue are to increase the number of Personal Protective Equipment (PPE) like earmuffs and improve the company layout.